Dynamic changes in the subcellular distribution of the tobacco ROS-producing enzyme RBOHD in response to the oomycete elicitor cryptogein - Noirot, Elodie; Der, Christophe; Lherminier, Jeannine; Robert, Franck; Moricova, Pavla; Kiêu, Kiên; Leborgne-Castel, Nathalie; Simon-Plas, Françoise; Bouhidel, Karim (Journal of experimental botany, 2014)
Plant NADPH oxidases, also known as respiratory burst oxidase homologues (RBOHs), have been identified as a major source of reactive oxygen species (ROS) during plant-microbe interactions. The subcellular localization of the tobacco (Nicotiana tabacum) ROS-producing enzyme RBOHD was examined in Bright Yellow-2 cells before and after elicitation with the oomycete protein cryptogein using electron and confocal microscopy. The plasma membrane (PM) localization of RBOHD was confirmed and immuno-electron microscopy on purified PM vesicles revealed its distribution in clusters. The presence of the protein fused to GFP was also seen in intracellular compartments, mainly Golgi cisternae. Cryptogein induced, within 1h, a 1.5-fold increase in RBOHD abundance at the PM and a concomitant decrease in the internal compartments. Use of cycloheximide revealed that most of the proteins targeted to the PM upon elicitation were not newly synthesized but may originate from the Golgi pool. ROS accumulation preceded RBOHD transcript- and protein-upregulation, indicating that ROS resulted from the activation of a PM-resident pool of enzymes, and that enzymes newly addressed to the PM were inactive. Taken together, the results indicate that control of RBOH abundance and subcellular localization may play a fundamental role in the mechanism of ROS production.
Keywords: buněčná membrána; Nicotiana; Nicotiana tabacum; reaktivní formy kyslíku; cryptogein; Microscopy, Confocal; protein trafficking; fungální proteiny; protein trafficking.; BY-2 cells; konfokální mikroskopie; respiratory burst oxidase homolog D (RBOHD); Reactive Oxygen Species; NADPH Oxidases; rostlinné proteiny; tabák; NADPH-oxidasy; reactive oxygen species; Plant Proteins; transmisní elektronová mikroskopie; Real-Time Polymerase Chain Reaction; Microscopy, Electron, Transmission; Cell Membrane; Phytophthora; kvantitativní polymerázová řetězová reakce; Fungal Proteins